Recontextualization of Ecological Verses of the Quran in Responding to Floods and Landslides in Sumatra in 2025 (Thematic Study of Ecological Verses) - Faza Aulia Putri; Jatim Jatim (Syaikhuna: Jurnal Pendidikan dan Pranata Islam, 2026)
The Major losses are often understood solely as natural events without linking them to theological-ecological dimensions. This study aims to explain the causal factors of the disaster, interpret the ecological verses of the Qur'an through a thematic (maudūʿī) approach, and articulate the relevance of its message as a basis for ecological ethics. This study uses a qualitative method based on literature (library research) by collecting and analyzing the Qur'an through interpretations of Quraish Shihab, Hamka, and al-Marāghī, combined with empirical disaster data. The results of the study indicate that the ecological framework in Quranic exegesis is categorized into roles: humans as khalīfah fī al-ardḍ, entrusted with safeguarding the earth; the prohibition of ifsād as the operational norm of this mandate; and fasād as an empirical diagnosis and a call to yarjiʿūn. These findings have implications for the basis of Islamic environmental ethics (tawḥīd, amānah, ʿadl), which can be implemented through fiqh al-bī'ah and by strengthening the ecological awareness of Muslim communities.